P5-S6.08 STD surveillance and control: do STD and family planning clinics matter?. (10th July 2011) - Doshi, S; Owusu-Edusei, K
Abstract : Background: Information on the potential impact of the presence of an STD and/or family planning (FP) clinic on STD surveillance and control is scant. In the study, we examine the impact of STD and/or publicly funded Title V, X, and XX FP clinics on county-level surveillance and control of three reportable STDs (chlamydia (CT), gonorrhoea (GC) and primary and secondary syphilis (P&S)) in Texas during 2000 and 2007. Specifically, we examined the following two questions: (1) Are the counties with STD/FP clinics reporting relatively more cases of STDs? (2) Does having STD service(s) (the presence of an STD/FP clinic) in a county matter? Methods: We used spatial regression to analyse the impact of STD/FP clinics on county-level STD morbidity using surveillance data on CT, GC, and P&S. the impact of STD/FP clinics on STD control was examined using a backward stepwise regression on the changes in incidence rates between 2000 and 2007. Dummy variables represented the presence of STD/FP clinic(s). Incidence rates were transformed into natural logs. County-level demographics for 2000 and 2007 were used as control variables. Results: The coefficients on the dummy variables representing the presence of STD/FP clinics were: 0.11 (95% CI 0.05 to 0.16, p<0.01) in 2000 and 0.07 (CI 0.02 to 0.12, p<0.01) in 2007 for CT; 0.13 (CI 0.05 to 0.20, p<0.01) in 2000 and 0.06 (CI −0.002 to 0.12, p<0.01) in 2007 for GC and 0.18 (CI 0.12 to 0.23, p<0.01) in 2000 for P&S (2007 was not significant). This implies that the transformed GC and CT rates in the counties with STD/FP clinics increased by at least 6% in 2000 and 2007, while P&S increased by 18% in 2000. The coefficient for the changes in rates between 2000 and 2007 were: −0.04 (CI 0.01 to −0.09, p<0.10) for CT; −0.08 (CI −0.02 to −0.14, p<0.01) for GC and −0.09 (CI −0.03 to −0.15, p<0.01) for P&S. Thus, the transformed incidence rates of GC and P&S reduced by 8% and 9%, respectively, between 2000 and 2007 for those counties that had at least one STD/FP clinic. Conclusion: The results from this ecological study are consistent with (but do not establish) a causal relationship between having an STD/FP clinic and improved surveillance and/or reduction in STDs at the county-level in Texas. However, the results suggest that STD/FP clinics play an important role in STD surveillance and control. Finer level analyses (such as census block or cities) may be able to establish a strong causal relationship.